ANALISIS DAMPAK PUTUSAN MAHKAMAH KONSTITUSI NOMOR 143/PUU-XXI/2023 DALAM PEMBENTUKAN NORMA BARU: Analysis Of The Impact Of The Constitutional Court Decision Number 143/PUU-XXI/2023 In Establishing A New Norm - Rana Sayyidah Nabilah; Yogo Pamungkas (Faculty of Law, Universitas Trisakti, 2025)
The Constitutional Court, in conducting judicial review, has the authority to decide cases by granting, rejecting, or declaring the petition inadmissible. Furthermore, the Constitutional Court may issue decisions declaring certain provisions conditionally unconstitutional, meaning the law must be interpreted under specific conditions. However, there are instances where the Constitutional Court not only interprets existing norms but also introduces new norms in its rulings. The problem of this article analyzes the Constitutional Court Decision Number 143/PUU-XXI/2023. The considerations of Constitutional Court Judges are evaluated for their conformity with Article 73 of Constitutional Court Regulation Number 2 of 2021. Decisions that add new norms are also reviewed for their conformity with these regulations. This research adopts a normative legal method with a descriptive approach, relying on secondary data comprising primary, secondary, and tertiary legal materials. Conclusions are drawn using deductive reasoning. The findings and the conclusion indicate that the Justices, in this case, incorporated new norms into their considerations, exceeding mere legal interpretation. The decision is deemed inconsistent with Article 73 paragraphs (3) and (4) of PMK 2/2021, which limits the Constitutional Court's authority in deciding judicial review cases.